Analisis Kerusakan Saluran Sekunder Daerah Irigasi Susoh Kabupaten Aceh Barat Daya - Dania, Arvi; Chaira, Chaira; Suciatina Silva, Cut (Jurnal Etnik: Ekonomi-Teknik, 2022)
The Susoh irrigation area is one of the irrigation areas in Sounthwest Aceh Regency, the Susoh Irrigation Area irrigates water with a standartd area of 5,793 Ha and a functional area of 2,571.24 Ha. However, with damage along the channel, the water needs are less than optimal for irrigating water in the rice fields. Damage to one of the irrigation buildings will affect the performance of the existing system, so in the secondary canal of the Susoh Irrigation Area it is necessary to do a research on channel damage analysis. Water discharge, water loss is also the amount of efficiency and effectiveness in the Susoh Irrigation Area. From the results of the analysis, it is known that the amount of water loss in the secondary canal in the Susoh Irrigation Area is 0.15696 m/s, the efficiency value is 77.67257% and the effectiveness value is only 51.79%. From the result of this analysis, it can be seen that the condition of the D.I Susoh secondary canal is mostly damaged, so it needs rehabilitation.